Wanita Muslimah dalam Problema Kehidupan Modern - M. Zainuddin (el Harakah: Jurnal Budaya Islam, 2001)
This paper describes how Muslim women face problems in the modern era. Modern life is characterized by technological sophistication and industrial advancement as well as the diminishing of the agrarian sector. The strengthening of rationalism and the emergence of individualism that has implications for the alliance signifies that existence. The problem faced by Muslim women today is a matter of modemization that leads to the demands of emancipation. Emancipation is the result of the demands of western women who feel unaccounted for and eliminated from men. Male dominance and arbitrary acts implicate the emergence of the demands of women's freedom are also excessive. The idea of equality of rights itself also contains a contradiction that is quite confusing in terms of concepts and applications in social laws and policies.   Tulisan ini memaparkan bagaimana muslimah menghadapi persoalan di era modern. Kehidupan modern dicirikan oleh sofistikasi teknologi dan kemajuan dibidang industri serta semakin berkurangnya sektor agraris. Menguatnya rasionalisme dan munculnya individualisme yang berimplikasi kepada alinasi menandai adanya itu. Problematika yang dihadapi wanita muslimah kini adalah masalah modemisasi yang mengarah pada tuntutan emansipasi. Emansipasi adalah akibat dari tuntutan kaum wanita barat yang merasa tidak mendapatkan tempat dan teralinasi dari kaum pria. Dominasi kaum pria dan pcrlakuan yang semena-mena berimplikasi munculnya tuntutan kebebasan kaum wanita yang juga berlebihan. Ide persamaan hak (equal rights) sendiri juga mengandung kontradiksi yang cukup membingungkan tern tarn a dalam hal konsep dan aplikasinya dalam undang-undang dan kebijakan sosial.